Positioning of Chinese time nouns and adverbs: Evidence from corpus, acceptability, and processing studies - Jia Yi Chen; Ying Su; Katsuo Tamaoka (PLoS ONE, 2025)
This study examines the syntactic placement and cognitive processing of time nouns and time adverbs in Mandarin Chinese, a language without overt tense morphology, highlighting how these temporal expressions interface with Chinese grammar. Study 1 analyzed a large-scale natural language corpus (BLCU Chinese Corpus) to determine the typical positions of time nouns and time adverbs relative to the subject. The results revealed distinct distributional patterns: time nouns occurred flexibly either before or after the subject, while time adverbs appeared predominantly in post-subject (sentence-internal) positions. Study 2 investigated native Mandarin speakers’ acceptability judgments of sentences with time expressions in various positions. Sentences in which time nouns followed the subject were rated as more acceptable and supported the canonical word order, whereas pre-subject time nouns were acceptable mainly in topicalized contexts. In contrast, time adverbs were strongly preferred in post-subject positions, with only a few exceptions where certain adverbs could be fronted. Study 3 examined the real-time comprehension of these structures using reaction time and accuracy. Results showed that sentences with time expressions in non-canonical positions incurred greater processing costs, while canonical post-subject placements facilitated faster and more accurate processing. These findings suggest that the human sentence processor is sensitive to structural preferences for temporal expressions, mirroring patterns in natural use and grammatical acceptability. By integrating corpus analysis, acceptability judgments, and psycholinguistic data, this study provides a comprehensive account of how time nouns and time adverbs are positioned and processed in Chinese, offering broader implications for understanding temporal reference in tenseless languages.